An observational study to evaluate the long‐term outcomes of treatment with etanercept in patients with plaque‐type psoriasis. (14th June 2016) - Luger, T.; Schopf, R.E.; Schwanke, A.; Langhammer, S.; Meng, T.; Löschmann, P.A.
Abstract: Background: There is an unmet need for long‐term, real‐life data on the effect of a drug‐free interval between treatment cycles in patients with plaque psoriasis being treated with etanercept, which is licensed for intermittent and continuous treatment. Objective: The aim of this study was to determine the average duration of the drug‐free interval between etanercept treatment cycles in patients with plaque psoriasis. Methods: This was a non‐interventional, open‐label, multicentre, prospective study in patients for whom the decision had already been made to initiate treatment with etanercept during routine practice in German centres. Clinical outcomes were documented over 36 months with study visits every 12 weeks. The primary endpoint was the duration of the treatment‐free interval between etanercept treatment cycles (24 weeks/cycle). Secondary endpoints assessed efficacy [Psoriasis Area and Severity Index (PASI), Body Surface Area (BSA), static Physician's Global Assessment (sPGA)], health‐related outcomes [EuroQol‐5 Dimensions (EQ‐5D), Dermatology Life Quality Index (DLQI)] and safety. Results: A total of 955 patients were enrolled from 224 centres; 926 of these were included in the safety analyses and 720 patients from the safety population were included in the efficacy analysis. The mean duration of drug‐free intervals was 12.9 ± 12.8 weeks. Efficacy and health‐related quality of life outcomes measures showed consistent improvement that occurred within 12 weeks of treatment with etanercept. There was a descriptive difference between the continuous and intermittent treatment subgroups, as subjects in the latter showed a deterioration at the first visit following an interval. However, retreatment with etanercept resulted in a clinical efficacy identical to the initial effect. The incidence of physician‐assessed, drug‐related adverse events and serious adverse events was 13.1% and 1.9%, respectively. Conclusion: The mean duration of drug‐free intervals was relatively short, most patients experienced improvements in disease activity and health‐related quality of life within 12 weeks of either continuous or intermittent treatment with etanercept, and there were no new safety signals. ClinicalTrials.gov identifier: NCT00708708.